Pengembangan Model Instrumen Penilaian Kinerja Dokter Spesialis Obsgyn Melalui Analisis Kinerja di Rumah Sehat Ibu Dan Anak Budi Kemuliaan - Setyorini, Titi (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2016)
The purpose of this studyis to develop an instrument that appropriate to measured Obstetrician and Gynecologist performance in Budi Kemuliaan Hospital through Performance Analysis. Descriptive study with qualitative method aims to constructed a Performance Appraisal’s Instrument. A convenience Informan of Obstetrician and Gynecologists and stakeholders in Budi Kemuliaan Hospital participated in this study. This study successfully developed a valid method to constructed a Performance Appraisal’s Instrument in Budi Kemuliaan Hospital by using Nominal Group Technique Method. A performance appraisal’s instrument contains 8 (eight) specific measurable criteria for Obstetrician and Gynecologists using the JCAHO’s six competencies to evaluated Medical Doctors performance that suitable for Budi Kemuliaan Hospital, with standards each specific measurable criteria and scoring categories.